2017
DOI: 10.1109/jiot.2017.2755980
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Routing Protocol for Low Power and Lossy Networks (RPL) in Large Scale Networks

Abstract: Abstract-With growing needs to better understand our environments, the Internet-of-Things (IoT) is gaining importance among information and communication technologies. IoT will enable billions of intelligent devices and networks, such as wireless sensor networks (WSNs), to be connected and integrated with computer networks. In order to support large scale networks, IETF has defined the Routing Protocol for Low power and Lossy Networks (RPL) to facilitate the multi-hop connectivity. In this paper, we provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…As a result, it is found that the mean end to end delay is decreased when using hop count objective function with a greater packet delivery ratio when using RSSI-ETX objective function. Such results are obtained when using OMNET++ simulator [15].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…As a result, it is found that the mean end to end delay is decreased when using hop count objective function with a greater packet delivery ratio when using RSSI-ETX objective function. Such results are obtained when using OMNET++ simulator [15].…”
Section: Introductionmentioning
confidence: 53%
“…This mechanism is known as trickle timer mechanism used by DIO message [26]. A trickle timer also determines the frequency of sending messages in the network [15].…”
Section: B Trickle Timermentioning
confidence: 99%
See 1 more Smart Citation
“…RPL was standardized for 6LoWPAN networks bringing the concept of IoT into real life. Since then, many studies have evaluated the performance of RPL and they have suggested some improvements to potential shortcomings and open issues [13,14]. In the literature, many research works have carried out on various aspects of RPL based wireless sensor networks (WSNs), such as load balancing, energy conservation, QoS support, and protocol optimization [15].…”
Section: Related Workmentioning
confidence: 99%
“…There are various existing surveys and investigational analysis on security and privacy issues in the IoT eco-system. The work of Liu et al [21] carried an extensive analysis on performance of routing based approach in large sensor networks. Here, the authors have reviewed the fundamental principal of routing and its control messages.…”
Section: Literature Surveymentioning
confidence: 99%